2022
DOI: 10.3390/medicina58050629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visual Cue Deprivation Balance Training with Head Control on Balance and Gait Function in Stroke Patients

Abstract: Background and Objectives: Visual cue deprivation is the instability of head control is increased. The purpose of this study is to investigate the effects of visual cue deprivation balance training by applying head control feedback to the balance and gait ability of stroke patients. Materials and Methods: The study was conducted on 41 patients diagnosed with hemiplegia due to stroke. Subjects were randomly assigned to any of the following groups: the experimental group, the experimental group, or the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These results may be due to the increasing difficulty factor of intermittent visual and auditory deprivation in the intervention program. Intermittent visual deprivation training aids older adults in distinguishing between somatosensory and vestibular sensory inputs, reducing overreliance on vision and improving their reactive ability [ 39 , 40 ]. In addition, our study intermittently deprived older adults of auditory input during training, and older adults were more focused on muscle strength and balance training [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results may be due to the increasing difficulty factor of intermittent visual and auditory deprivation in the intervention program. Intermittent visual deprivation training aids older adults in distinguishing between somatosensory and vestibular sensory inputs, reducing overreliance on vision and improving their reactive ability [ 39 , 40 ]. In addition, our study intermittently deprived older adults of auditory input during training, and older adults were more focused on muscle strength and balance training [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of myopia in postural control during walking can be based on kinematic parameters. It has been demonstrated that abnormalities in body postural control, such as those seen in stroke and scoliosis patients, result in various changes in gait kinematic data ( 3 , 8 , 9 ). The kinematic analysis can be used to study the temporal and spatial patterns of the limb movements during walking.…”
Section: Introductionmentioning
confidence: 99%